Analysis of Fair Price Valuation of Shares in Investment Decision Making in Islamic Banking Issuers on the Indonesia Stock Exchange (Years 2018-2021) - Mohammad Ibnu Hibban; Guntur Kusuma Wardana (Budapest International Research and Critics University, 2022)
In determining value (value) or commonly known as valuation, it has become mandatory for individuals or companies to express the value they have created. The main part of value extension in the valuation process is very necessary to be controlled by an investment analyst, this becomes important so that an investor can know what company has the potential to increase the value of the investment when investing. Moreover, the main goal of an investor is to seek profit or increase the value of what is invested. Therefore, the issue of value and investment decisions is an important thing to note for investors. The purpose of this study is to find out the fair value of Islamic banking shares on the Indonesia Stock Exchange so that it makes it easier to make investment decisions. From that background, this study was conducted with the title